The Influence of Compensation on Human Resource Performance in the Environmental Services of South Halmaera District - Sumual, Tineke; Watung, Sjeddie; Sumual, Shelty; Jamil, Jumrah; Repi, Heidi Kristian (MultiTech Publisher, 2023)
This research intends to investigate and assess how compensation affects the performance of human resources in the Environmental Department of South Halmahera Regency. The method in writing this article is a quantitative research technique, namely building theory by testing the relationship between variables. These variables can be measured and explained as instruments with relevant statistical analysis that can be interpreted. The benefit the purpose of this essay is to ascertain how compensation affects the performance of human resources in the Environmental Department of South Halmahera Regency. The research results reveal that this can be achieved well if the human resources within the company/organization are handled by appropriate management of human resources. It was determined that whenever there was a rise in compensation, employee morale increased. Suggestions require adjustments to compensation to increase employee morale at the South Halmahera Regency Environmental Service, both now and in the future and it is hoped that in the future it will be further improved to achieve organizational goals.